Towards a Comparative Framework of Demographic Resilience. (September 2020) - Capdevila, Pol; Stott, Iain; Beger, Maria; Salguero-Gómez, Roberto
Abstract : In the current global biodiversity crisis, the development of tools to define, quantify, compare, and predict resilience is essential for understanding the responses of species to global change. However, disparate interpretations of resilience have hampered the development of a common currency to quantify and compare resilience across natural systems. Most resilience frameworks focus on upper levels of biological organization, especially ecosystems or communities, which complicates measurements of resilience using empirical data. Surprisingly, there is no quantifiable definition of resilience at the demographic level. We introduce a framework of demographic resilience that draws on existing concepts from community and population ecology, as well as an accompanying set of metrics that are comparable across species. Highlights: The global biodiversity crisis demands a broad understanding of the ability of species to respond to external disturbances caused by global change. A common framework to quantify, compare, contrast, and predict the resilience of species to global change is urgently needed. Resilience includes the resistance of populations to change after disturbance and their recovery from it. Measurements of short-term population growth following disturbances, and any of its longer-term consequences, allow quantification of demographic resilience. Quantifying demographic resilience with common semantic and numeric definitions enables comparisons of resilience across species, enabling us to predict their responses to disturbances.